Importance of Soft Skills on Career Development - Wickramasinghe, U. V. K. W.; Darshani, R. K. N. D. (Department of of Human Resource Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka, 2021)
Soft skills are important to be successful in professional life. It became an essential part of the career development process in today's business context. People who are having these soft skills can easily capture new career opportunities than the others who are not qualified with these personal qualities. It can be added value to our professional life. But there is a soft skill gap in the job market. The purpose of this research was to identify the most prominent soft skills in the job market and to examine the importance of soft skills on career development. This study is done based on the Sri Lankan context compared with literature based on different countries. This study is based on the qualitative-deductive approach, and this is a cross-sectional study. Data was collected via a focus group discussion and structured interviews with the participation of students and employers. The researcher has identified personal perceptions, organizational support, and demand for soft skills in the job market as independent variables and career development as the dependent variable. So based on the findings, the researcher has identified communication skills, leadership skills, empathy, emotional intelligence, and adaptability as the most prominent soft skills in the job market and benefits of having those personal qualities to develop their career. And the researcher is recommended to establish soft skills as a subject for students in their academic programs, build friendly work environments, and provide more training and development programs to develop soft skills. This study would provide direction to HR practitioners, students, employers, and to future researchers.
Keywords: Career Development, Soft Skills